International Legal Acts Regulating Convict Labor - Koval, T. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article examines the views on punishment and the practice of their implementation, analyzes the formation of international legal standards for the treatment of prisoners, the rights and freedoms of convicts.